2015
DOI: 10.1016/j.jpainsymman.2014.10.020
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Factors Associated With the Use of a Dedicated Supportive Care Center Telephone Triaging Program in Patients With Advanced Cancer at a Comprehensive Cancer Center

Abstract: In this study, we found that overall utilization of the SCCTP by ACPs referred to palliative care was relatively low at 28.7%. The use of the SCCTP was particularly poor among the IPs on discharge. Patients who used SCCTP had worse pain, fatigue, depression, and well-being scores and better delirium scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…This model also solidifies the independent role played by palliative care teams in cancer care rather than being seen as an appendage of individual oncology clinics. To prevent symptom crises proactively, a centralized clinic may also facilitate the coordination of telehealth interventions …”
Section: Innovative Models Of Care Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…This model also solidifies the independent role played by palliative care teams in cancer care rather than being seen as an appendage of individual oncology clinics. To prevent symptom crises proactively, a centralized clinic may also facilitate the coordination of telehealth interventions …”
Section: Innovative Models Of Care Deliverymentioning
confidence: 99%
“…To prevent symptom crises proactively, a centralized clinic may also facilitate the coordination of telehealth interventions. 103,104 The main limitations of freestanding outpatient clinics are budgetary and funding restrictions. Consideration needs to be given to this from the outset, with a strong business model and planning for additional resources, space, and clinicians over time.…”
Section: Outpatient Clinicsmentioning
confidence: 99%
“…Our study showed several factors that seem to correlate with an increased number of phone calls; while physical suffering did not play a relevant role in triggering contacts, psychosocial and several clinical factors did. There are relatively few publications on the use of telephone programs in palliative care, with the data showing contacts based on requests for support services, medical assistance due to changes in patients' overall condition, and concerns regarding symptoms such as anxiety, depression, and physical distress (Pimentel et al, 2015;Baird-Bower et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…41 It has been reported also that simple interventions such as phoning patients to follow-up after interventions done during the clinical visit may result in improved symptom expression. 42 In this study we did not measure if calls were performed or not, and the quantity and content of them if they were done to the patients as a way of following the symptoms after interventions. Further studies are encouraged to evaluate the value of this type of interventions.…”
Section: Discussionmentioning
confidence: 99%